Pengaruh environmental, social, and governance (ESG), green innovation, dan eco-efficiency terhadap nilai perusahaan dengan kinerja keuangan sebagai moderasi - Wahyu Widiyanti (LPMP Imperium, 2025)
Abstract This study aims to analyze the effects of Environmental, Social, and Governance (ESG), green innovation, and eco-efficiency on firm value, as well as the moderating role of financial performance (Return on Assets/ROA). The population comprises non-financial manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023, selected using a purposive sampling method. The analysis begins with descriptive statistics, followed by normality testing and classical assumption tests (autocorrelation, multicollinearity, and heteroscedasticity), and continues with multiple linear regression analysis. The findings reveal that green innovation and eco-efficiency have a significant positive impact on firm value, whereas ESG disclosure has an adverse effect. ROA, as a moderating variable, does not show a substantial effect, except in its relationship with green innovation, which shows a negative effect. Additionally, firm size and leverage positively influence firm value. These results suggest that the effectiveness of sustainability strategies depends on internal readiness and market context to deliver added value to the company. Public interest statements This study analyzes the influence of ESG, green innovation, and eco-efficiency on firm value, with financial performance as a moderating variable. The findings provide a basis for corporate policies focused not only on financial profit but also on sustainability and social responsibility. The results are expected to guide investors, regulators, and businesses in promoting sustainable practices. .